THE FERTILITY OF THE MEADOW SOILS OF THE SHAHRIKHONSOY SPREAD AND ITS CHANGES UNDER THE INFLUENCE OF HUMAN FACTORS (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
This work is devoted to the assessment of the fertility of meadow saz soils in the upper part of the Shahrikhonsoy plain of East Fergana and its changes under the influence of the human factor. The study scientifically substantiates the fact that under irrigated farming conditions, agro-ameliorative measures such as land leveling, plowing, irrigation and salt leaching, drainage and fertilization significantly change the structure and main agrochemical properties of the soil, resulting in the formation of a new (different from natural) regime of soil formation processes. Field research was conducted on the basis of placing soil sections along a geochemical-geographical section and comparing them with analytical indicators. The results show that at the initial stage of irrigation and development, the mineralization of organic matter increases, and at subsequent stages, the amount of humus and nutrients can stabilize or increase due to agrotechnical measures and crop residues. The mechanical composition of the soils of the region is mainly medium and light loam, and the reclamation condition is satisfactory; due to the limited absorption of phosphorus, it is noted that it accumulates in the soil in various forms, and potassium has a relatively stable supply level. The results of the work are of practical importance for managing the fertility of irrigated lands, optimizing agrochemical supply, and planning reclamation measures in accordance with regional conditions.